Oral Health–related Beliefs, Behaviors, and Outcomes through the Life Course. (July 2016) - Broadbent, J.M.; Zeng, J.; Foster Page, L.A.; Baker, S.R.; Ramrakha, S.; Thomson, W.M.
Complex associations exist among socioeconomic status (SES) in early life, beliefs about oral health care (held by individuals and their parents), and oral health–related behaviors. The pathways to poor adult oral health are difficult to model and describe, especially due to a lack of longitudinal data. The study aim was to explore possible pathways of oral health from birth to adulthood (age 38 y). We hypothesized that higher socioeconomic position in childhood would predict favorable oral health beliefs in adolescence and early adulthood, which in turn would predict favorable self-care and dental attendance behaviors; those would lead to lower dental caries experience and better self-reported oral health by age 38 y. A generalized structural equation modeling approach was used to investigate the relationship among oral health–related beliefs, behaviors in early adulthood, and dental health outcomes and quality of life in adulthood (age, 38 y), based on longitudinal data from a population-based birth cohort. The current investigation utilized prospectively collected data on early (up to 15 y) and adult (26 and 32 y) SES, oral health–related beliefs (15, 26, and 32 y), self-care behaviors (15, 28, and 32 y), oral health outcomes (e.g., number of carious and missing tooth surfaces), and oral health–related quality of life (38 y). Early SES and parental oral health–related beliefs were associated with the study members' oral health–related beliefs, which in turn predicted toothbrushing and dental service use. Toothbrushing and dental service use were associated with the number of untreated carious and missing tooth surfaces in adulthood. The number of untreated carious and missing tooth surfaces were associated with oral health–related quality of life. Oral health toward the end of the fourth decade of life is associated with intergenerational factors and various aspects of people's beliefs, SES, dental attendance, and self-care operating since the childhood years.